Avaliação dos impactos da implantação de um teste treponêmico automatizado na rotina de triagem sorológica de doadores de sangue na Hemorrede do estado do Ceará - Benevides Sá Junior, José Newton (2022)
Syphilis is an infectious disease, with a chronic aspect, that has challenged humanity probably since its beginning. Despite the existence of treatment, in the last decade, the number of syphilis cases has been resurfacing in an alarming way in Brazil, now being considered as a reemerging disease. In addition to being a highly sexually transmissible disease, it also has proven transfusional transmission, including being part of the mandatory laboratory screening in the current blood cycle policy, according to the legislation in force in the country, which includes blood donation and distribution of blood components. Despite notable advances in transfusion safety due to several factors, including the use of more advanced methods of greater sensitivity for donor serological screening, in many blood banks non-treponemal tests, such as VDRL/RPR, are still routinely used to the laboratory detection of syphilis, which have low sensitivity in the primary phase of the disease. In addition, they are still poorly compatible with automation systems, which makes their scalability and implementation difficult for high-demand health services and a large number of samples. In October 2019, an automated treponemal test was introduced in the serological screening of Hemorrede do Ceará, based on the electrochemiluminescence (ECLIA) methodology, with high sensitivity in the primary phase of the disease, thus modifying laboratory routines and causing an increase in detection rates. This study sought to evaluate the impacts caused by this implantation, evaluating the consequences of the increase in the proportion of reactive samples for syphilis in the 12 months following the beginning of its use, comparing them with an equivalent previous period of 12 months, as well as knowing the profile of reactive donors and follow up on their subsequent examinations. The study was carried out through the approval of the Ethics and Research Committee of the Hematology and HemotherapyCenter of Ceará, under the opinion of No. 4.345.218, CAAE 22873219.0.0000.8152, the data being collected in order to guaran-tee or anonymity to two donors and results obtained interpreted collectively. The results of the screening serologies for syphilis of 194,913 donations that took place at the Hematology and HemotherapyCenter of Ceará, between October 2018 and October 2020, were evaluated, of which 102,212 were submitted to the non-treponemal test (RPR) and 91,913 to the trepone-mal test (ECLIA), in different and non-concurrent periods, as described above. The results obtained showed seroreactivity for syphilis in 503/102,212 (0.5%) to RPR and in 1,003/91,913 (1.1%) to ECLIA. The profile of donors reactive to ECLIA showed that the majority were residents of the macro-region of Fortaleza 561/1,003 (55.9%), male 589/1,003 (58.7%), composed of young adults between 18-29 years old (279 /1,003, 27.8%), 30-39 years old (279/1,003, 27.8%), with complete high school (398/1,003, 39.7%), single marital status (513/1,003, 51.2 %), self-declared as brown/brown (721/1,003, 71.9%). Regarding the donation history, 376/1,003 (37.5%) were first-time donors and 627/1,003 (62.5%) were re-peat donors. Of the donors reactive to ECLIA, in the screening phase, 721/1,003 (71.9%) re-turned to the service for diagnostic tests until July 2021, of which 650/721 (90.2%) replicated the result reactive for syphilis while 71/721 (9.9%) were considered non-reactive. Of these, after applying the evaluation protocols for the rehabilitation of these donors, only 17/721 (2.4%) were characterized as false-positive reactions, and therefore, released to make new blood donations and the remainder (704/721, 97 .6%) definitively rejected for new donations. Furthermore, it was carried out a comparative analysis for basic demographic parameters be-tween the Reactive group with data from a blood donor group of 9,897 individuals from-Hemoce Fortaleza obtained between January and December 2020 (Programme for Serosur-veillance of COVID-19), which found that reactive individuals presented a distinct age profile and a higher proportion of Females compared to the control group (41.2% vs 37.7%). By conclusion, the new method used in serological triage (ECLIA) caused an increase in the prevalence of sero-reactivity for syphilis in relation to the non-treponemal method (RPR) previously used, with the majority being two reactive candidates composed of young adults, with ages between 18 and 39 years old, male, single, self-declared dark or brown and with a full middle age.